Unveiling the mechanisms and secrets of chemoselectivities in Au(i)-catalyzed diazo-based couplings with aryl unsaturated aliphatic alcohols. Issue 17 (14th August 2018) - Pei, Guojing; Liu, Yuxia; Chen, Guang; Yuan, Xiangai; Jiang, Yuan-Ye; Bi, Siwei
Abstract : The mechanisms and origins of the unsaturated-aliphatic-alcohols-modulated chemoselectivity of Au-catalyzed carbene transfers from diazo compounds are disclosed by DFT studies. Abstract : Density functional theory (DFT) calculations have been conducted to unravel the mechanisms and chemoselectivities of Au-catalyzed diazo-based couplings with phenyl unsaturated aliphatic alcohols: the propargyl alcoholBa resulting in the [4 + 1]-cycloaddition productP 4a and the allyl alcoholDb giving the [2, 3]-σ rearrangement speciesP 5b .P 4a formation involves a catalyst interaction with phenyldiazoacetate, N2 release, a hydroxyl O nucleophilic attack ofBa, a [1, 4]-H shift, coordination isomerization, 5- endo -dig cyclization, a [4, 1]-H shift and a H2 O-assisted [1, 3]-H shift. After the [4, 1]-H shift, the slightly less favorable five-membered ring-opening possibly follows to afford traceP 5a ([2, 3]-σ rearrangement product), which would be kept in solution due to subsequent irreversible evolution. In addition, theBa -involved chemoselectivity was probed and explained as follows: (i) both large H(hydroxyl)⋯C(carbene) electrostatic repulsion and strong three-membered ring strain involved in the TS make the formation of the O–H insertion productP 1a difficult and (ii) the nucleophilic attack from the C 2 atom ofBa brings about a structural twisting and thus increases the energy penalty forming the cyclopropenation productP 2a . On the other hand, compared with the sp-C 2 atom ofBa, the sp 2 -C 2 atom ofDb greatly facilitates the five-membered ring-opening step because of the presence of an extra pπ–pπ orbital overlap and eventually providesP 5b exclusively.